Global Unions, Global Business: Global Union Federations and International Business - McIlroy, John (Labour / Le Travail, 2010)
The article reviews the book, "Global Unions, Global Business: Global Union Federations and International Business," by Richard Croucher and Elizabeth Cotton.
Keywords: BOOKS -- Reviews; COTTON, Elizabeth; CROUCHER, Richard; GLOBAL Unions, Global Business: Global Union Federations & International Business (Book); INTERNATIONAL labor activities; Nonfiction